Cord Blood Banking Standards: Autologous Versus Altruistic - Armitage, Sue (Frontiers in Medicine, 2016)
Cord Blood (CB) is either donated to public CB banks for use by any patient worldwide for whom it is a match, or stored in a private bank for potential autologous or family use. It is a unique cell product that has potential for treating life-threatening diseases. The majority of CB products used today are for hematopoietic stem cell transplantation and are accessed from public banks. CB is still evolving as a hematopoietic stem cell source, developing as a source for cellular immunotherapy products, such as natural killer, dendritic and T-cells, and fast emerging as a non-hematopoietic stem cell source in the field of regenerative medicine. This review explores the regulations, standards and accreditation schemes that are currently available nationally and internationally for public and private CB banking. Currently, most of private banking is under regulated as compared to public banking. Regulations and standards were initially developed to address the public arena. Early responses from the medical field regarding private CB banking was that at the present time, because of insufficient scientific data to support autologous banking and given the difficulty of making an accurate estimate of the need for autologous transplantation, private storage of CB as “biological insurance” should be discouraged (Royal College of Gynecology 2001, American Academy of Pediatrics 2007; Ballen et al., 2008). To ensure success and the true realization of the full potential of CB, whether for autologous or allogeneic use, it is essential that each and every product provided for current and future treatments meets high-quality, international standards.